Evaluation of salivary tumor necrosis factor-alpha in patients with the chronic periodontitis: A case-control study - Hojatollah Yousefimanesh; Robati Maryam; Jahangirnezhad Mahmoud; Ghafourian Boroujerdnia Mehri; Taghipour Mohsen (Wolters Kluwer Medknow Publications, 2013)
Context: Periodontitis is a chronic infectious disease that leads to inflammation of the tissues supporting the teeth, bone loss, attachment loss progressively. In chronic periodontitis for starting the host response and inflammatory reaction, the presence of the infectious agent is necessary. Aims: One of inflammatory factors is tumor necrosis factor-alpha (TNF-α) that appear to be important in the destruction of periodontal tissues that were examined in this study. Materials and Methods: This study was performed in the laboratory and case-control study. The samples of study collected from 30 individuals with chronic periodontitis and 30 healthy controls that matched for age and sex, together. Unstimulated saliva samples were collected from patients and then TNF-α level were measured by enzyme-linked immunosorbent assay and were compared with the control group. Statistical Analysis Used: In this study for statistical analysis, Mann-Whitney was used. Results: There were differences in mean salivary concentrations of TNF-α in controls and patients. The average concentration in the case group was 9.1 (pg/ml) and the control group was 8.7 (pg/ml), but there was no significant difference between case and control groups (P > 0.05). Conclusions: The results of this analysis showed no significant relationship between two groups TNF-α concentration.This biomarker can not seem to be a good index to evaluate or predict periodontal disease.